Penguatan Ekonomi Kreatif Melalui Branding Produk Lokal Berbasis Cerita Rakyat dan Budaya Daerah - Liputo, Burhan; Hamka, Hamka; Asrul, Asrul (-, 2025)
The development of the creative economy in Indonesia shows great potential as a driver of national economic growth rooted in local culture and creativity. However, many micro, small, and medium enterprises (MSMEs) are still unable to develop strong and sustainable branding strategies. This article discusses efforts to strengthen the creative economy through local product branding that highlights folklore and regional culture as the foundation of identity. The research method uses a descriptive qualitative approach with data collected through observation, interviews, and literature studies. The findings indicate that integrating local cultural elements with modern marketing strategies can generate economic added value while also strengthening cultural preservation. In conclusion, folklore-based branding is not only a business strategy but also a form of cultural diplomacy that enhances the position of local products in the global market.